Exploring the Utilization of Artificial Intelligence in Nursing Education in a Tertiary Institution: A Case Study of Al-hikmah University, Ilorin, Nigeria - Abdulmumeen Ibrahim O*; Eze Suleiman M; Ismaeel Ibraheem O; Ayinla Kazeem A; Imam Rasheedah T; Abubakar Maryam K (Trends in Computer Science and Information Technology, 2025)
Abstract Introduction: Exploration of Artificial Intelligence (AI) in tertiary education focusing on its impact on learning outcomes and practical skill development serves as a strong metric for evaluating alignment with educational standard. AI-based tools such as virtual simulations and intelligent tutoring systems are explored as innovative approaches to addressing challenges in traditional nursing education, such as limited clinical placements and the need for personalized learning. Aim: This study is aimed at assessing the extent of AI integration, identifying implementation challenges, and evaluating its potential benefits on students’ academic performance, clinical decision-making, and skill acquisition. Methodology: A descriptive cross-sectional design was employed, with a sample of 165 participants (160 students and 5 Academic Staff). Data were collected using structured questionnaires and analyzed using t - tests and ANOVA to evaluate the hypotheses. Results: Students exposed to AI reported significantly improved learning outcomes, including higher academic performance and better clinical decision-making skills (t = 3.57, p < 0.001). Additionally, those engaged in AI-driven clinical simulations demonstrated better practical skill development compared to those trained with traditional methods (F = 10.32, p < 0.001). Key findings include limited access to AI tools, inadequate training, poor internet connectivity, and financial constraints. Conclusion: AI integration holds substantial promise for enhancing nursing education at Al-Hikmah University. Increased access to AI resources, providing faculty and student training, improving technological infrastructure, and formally integrating AI into the nursing curriculum. AI has the potential to transform nursing education by providing scalable, accessible, and personalized learning experiences, essential for preparing students for the complexities of modern healthcare.